Molecular survey and phylogenetic analysis of Bartonella sp., Coxiella sp., and hemoplamas in pudu (Pudu puda) from Chile: first report of Bartonella henselae in a wild ungulate species - Hidalgo-Hermoso, Ezequiel; Sepúlveda-García, Paulina; Cabello, Javier; Celis, Sebastian; Valencia, Carola; Ortiz, Carolina; Kemec, Ignacio; Moreira-Arce, Dario; Orsola, Miguel; Canales, Nivia; Garnham, Antonio; Vera, Frank; et al. (Frontiers in Veterinary Science, 2023)
Recent evidence shows a high diversity of infectious agents in wildlife that represent a threat to human, domestic and wild animal health. In Chile, wild populations of the most common cervid species, pudu (Pudu puda), have been reported as hosts for novel pathogens such as Mycoplasma ovis-like and a novel ecotype of Anaplasma phagocytophilum. A better understanding of the epidemiology of this group and other intracellular bacteria that might have cervids as hosts, will enlighten their population relevance. The aim of this study was to determine the occurrence and genetic diversity of Bartonella spp., haemotropic mycoplasmas, and Coxiella burnetii in pudus from Chile. The DNA was extracted from the blood samples of 69 wild free-ranging and 30 captive pudus from Chile. Real time (nouG gene for Bartonella and IS1111 element for C. burnetii) and conventional PCR (16S rRNA for haemotropic Mycoplasma spp. and rpoB, gltA, ITS for Bartonella spp.) in combination were used for pathogen screening and molecular characterization. DNA of Bartonella spp. was detected in 10.1% [95% CI (5.2-18.2%)] samples; haemotropic Mycoplasma spp. in 1.7% [95% CI (0.08-10.1%)]; and C. burnetii in 1.0% [95% CI (0.05-6.3%)]. Two sequenced samples were identified as Mycoplasma ovis-like and one free-ranging pudu was positive to C. burnetii. While one captive and two free ranging pudus were positive to Bartonella henselae, one wild pudu was co-positive to B. henselae and Bartonella sp. similar to bartonellae identified in ruminants. To the best of our knowledge, this is the first report of B. henselae in wild ungulate species and of C. burnetii and Bartonella spp. in wild ungulate species in South America. Further research will be necessary to evaluate the potential role of pudu as reservoirs of infection and identify the sources for disease transmission amongst wild, domestic animals and humans.